Clinical and Microbial Etiology Characteristics in Pediatric Urinary Tract Infection - Lu, Jiandong; Liu, Xiaozhu; Wei, Yi; Yu, Chengjun; Zhao, Jie; Wang, Ling; Hu, Yang; Wei, Guanghui; Wu, Shengde (Frontiers in Pediatrics, 2022)
Background: Urinary tract infection (UTI) is a common occurrence in children. UTI and urological malformations are intimately linked. However, whether urinary tract malformations affect the clinical features of pediatric UTI remains unclear. The purpose of this study was to characterize the clinical features and microbial etiology of UTI in children. Methods: We retrospectively reviewed the records of 741 patients with UTI treated at the Chongqing Medical University Affiliated Children's Hospital between 2015 and 2020. Patients with and without urological malformations were compared using propensity score matching (PSM). Results: Escherichia coli was the most common causative microorganism of UTI, accounting for 40.5% of infections. 122 patients (16.5%) had urological malformations. PSM identified 122 matched pairs of patients with or without urological malformations. The proportion of patients with UTI caused by atypical microorganisms was significantly higher in patients with urological malformations (P=0.048). Children with urological malformations showed longer duration of intravenous antibiotic treatment (P= 0.010), higher cost of treatment (P<0.001), and higher prevalence of recurrence (23.8% vs. 10.7%, P<0.001), compared with the normal group. Conclusion: Children with urological malformations are more likely to develop UTI with atypical microorganisms. Appropriate imaging examination and urine culture are strongly recommended for the diagnosis and management of pediatric UTI.